ANALYZING THE BRAND POSITIONING AND MARKET SEGMENTATION OF PT. DHARMABHAKTI EKAPERDANA HOUSING - Ombuh, Natanael Matthew Ombuh; Worang, Frederik G. Worang; Saerang, Regina T. Saerang (Universitas Sam Ratulangi, 2024)
This research examines the brand positioning and market segmentation strategies of PT Dharmabhakti Ekaperdana, a prominent housing developer in North Sulawesi, particularly North Minahasa. The study aims to understand how the company distinguishes itself from competitors and effectively targets its primary market. By employing qualitative research methods, including interviews with key informants and analysis of primary data, the study identifies the core values and mission of PT Dharmabhakti Ekaperdana and evaluates their impact on brand positioning. The research highlights the company's commitment to creating competitive, reliable, and highly professional local human resources, establishing a robust business network, and ensuring sustainability and customer satisfaction. The study also explores how PT Dharmabhakti Ekaperdana tailors its marketing strategies based on demographic, psychographic, and geographic segmentation criteria. The research acknowledges the result within interview and documentation process using 6 questions according to Brand Positioning and Market Segmentation variable. This study contributes valuable insights into the strategic marketing management of PT. Dharmabhakti Ekaperdana and its efforts to maintain competitiveness and trust in the housing development sector. Key Word: Brand Positioning, Market Segmentation